Upper rate limits for one-to-one auditory-motor coordination involving whole-body oscillation: a study of street dancers and non-dancers - Miura, A.; Fujii, S.; Okano, M.; Kudo, K.; Nakazawa, K. (The Journal of Experimental Biology, 2018)
The capacity for auditory-motor coordination (AMC) is shared by several species, among which humans are most flexible in coordinating with tempo changes. We investigated how humans lose this tempo flexibility at their upper rate limit, and the effect of skill level on this phenomenon. Seven skilled street dancers, including a world champion, and 10 non-dancers were instructed to bend their knees according to a metronome beat in a standing position at eight constant beat frequencies (3.8-5 Hz). Although maximum frequency of movement during the task was 4.8 Hz in the non-dancers and 5.0 Hz in the dancers, the rate limit for AMC was 4.1 Hz in the non-dancers and 4.9 Hz in the dancers. These results suggest that the loss of AMC was not due to rate limit of movement execution but rather to a constraint on the AMC process. In addition, mediation analysis revealed that a kinematic bias (i.e. the extent of knee flexion during the task) causally affected the extent of phase wandering via mediating factors (e.g. the extent to which movement frequency was reduced relative to the beat frequency). These results add evidence that gravity acts as constraint on AMC involving vertical rhythmic movement.